Risk Factors for Stunting among Toddler (2-5 years old) - Handayani, Septi; Setyawati, Dewi; Rosidi, Ali; Ernawati, Ernawati (Media Keperawatan Indonesia, 2023)
Stunting is a chronic nutritional problem characterized by height or body length that is not proportional to age. The prevalence of stunting at the Bandarharjo Health Center is the highest in Semarang City in 2021 reaching 534 children under five. Low nutritional intake and genetic and economic factors are some of the factors that influence the incidence of stunting. The study aimed to determine the risk factors for stunting in toddlers at the Bandarharjo Health Center. This study used cross-sectional with a sample of 51 families with stunting toddlers recorded at the Bandarharjo Health Center. The selection of subjects in total sampling is then data obtained through questionnaires. The data were analyzed using the chi-square test.This study showed that the Family Per Capita Income was low at 9.8%, and the Family Per Capita Income was high at 90.2%; the results showed that family income was not significantly related (p = 0.368) with the incidence of stunting. Conclusion: The level of Low Family Per Capita Income in children under the age of 2 – 5 years in the working area of the Bandarharjo Health Center Semarang City is 9.8%, and the level of High Family Per Capita Income is 90.2% and there is no relationship between Family Per Capita Income and the incidence of stunting in children under the age of 0 - 24 month in the working area of the Bandarharjo Health Center, Semarang City.